Accelerated 4D phase contrast MRI in skeletal muscle contraction. Issue 5 (5th March 2018) - Mazzoli, Valentina; Gottwald, Lukas M.; Peper, Eva S.; Froeling, Martijn; Coolen, Bram F.; Verdonschot, Nico; Sprengers, Andre M.; van Ooij, Pim; Strijkers, Gustav J.; Nederveen, Aart J.
Abstract : Purpose: 3D time‐resolved (4D) phase contrast MRI can be used to study muscle contraction. However, 3D coverage with sufficient spatiotemporal resolution can only be achieved by interleaved acquisitions during many repetitions of the motion task, resulting in long scan times. The aim of this study was to develop a compressed sensing accelerated 4D phase contrast MRI technique for quantification of velocities and strain rate of the muscles in the lower leg during active plantarflexion/dorsiflexion. Methods: Nine healthy volunteers were scanned during active dorsiflexion/plantarflexion task. For each volunteer, we acquired a reference scan, as well as 4 different accelerated scans (k‐space undersampling factors: 3.14X, 4.09X, 4.89X, and 6.41X) obtained using Cartesian Poisson disk undersampling schemes. The data was reconstructed using a compressed sensing pipeline. For each scan, velocity and strain rate values were quantified in the gastrocnemius lateralis, gastrocnemius medialis, tibialis anterior, and soleus. Results: No significant differences in velocity values were observed as a function acceleration factor in the investigated muscles. The strain rate calculation resulted in one positive (s+ ) and one negative (s− ) eigenvalue, whereas the third eigenvalue (s3 ) was consistently 0 for all the acquisitions. No significant differences were observed for the strain rate eigenvalues as a function of acceleration factor. Conclusions: Data undersampling combined with compressed sensing reconstruction allowed obtainment of time‐resolved phase contrast acquisitions with 3D coverage and quantitative information comparable to the reference scan. The 3D sensitivity of the method can help in understanding the connection between muscle architecture and muscle function in future studies.